2020 15th IEEE Conference on Industrial Electronics and Applications (ICIEA) 2020
DOI: 10.1109/iciea48937.2020.9248347
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Space Classification Using Cascaded LSTM

Abstract: Indoor space classification is an important part of localization that helps in precise location extraction, which has been extensively utilized in industrial and domestic domain. There are various approaches that employ Bluetooth Low Energy (BLE), Wi-Fi, magnetic field, object detection, and Ultra Wide Band (UWB) for indoor space classification purposes. Many of the existing approaches need extensive pre-installed infrastructure, making the cost higher to obtain reasonable accuracy. Therefore, improvements are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…As an example, in [31], the authors used training data coming from UAV, Wi-Fi and cellular base stations. In [45], the authors used a fusion of Wi-Fi RSS and geomagnetic field (GMF) data. The authors also found that by using only RSS or GMF data, the accuracy of their ML model deteriorated.…”
Section: Training Data 1) Size Of Training Datasetmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, in [31], the authors used training data coming from UAV, Wi-Fi and cellular base stations. In [45], the authors used a fusion of Wi-Fi RSS and geomagnetic field (GMF) data. The authors also found that by using only RSS or GMF data, the accuracy of their ML model deteriorated.…”
Section: Training Data 1) Size Of Training Datasetmentioning
confidence: 99%
“…Many different variations of RNNs have been used for propagation modeling purposes, such as the echo state networks (ESNs), [57], Elman RNNs [53], standard RNNs [32], [58] and gated RNNs that use a gated recurrent unit (GRU) instead of a standard recurrent unit cell [31], [32]. The most important and popular type of RNN is the long short-term memory (LSTM) RNN that can capture longer dependencies in the input data, compared to the other types of RNNs [30], [32], [33], [45], [59]. In propagation modeling problems, the input sequence to the RNN is usually spatial [32] or temporal [31], [58].…”
Section: A Ann-based Modelsmentioning
confidence: 99%